Exploring Nurses Satisfaction with Pain Assessment Training Programs: Factors Contribute in Transfer of Training into Nursing Practice (Journal of Engineering and Health Sciences, 2024)
The effective management of pain is a critical component of patient care, and nurses play a pivotal role in pain assessment and management. This study aims to explore nurses' satisfaction with pain assessment training programs and identify the factors that contribute to the transfer of training into nursing practice. Utilizing a qualitative phenomenological approach, the research will encompass quantitative surveys to measure nurses' satisfaction levels and qualitative interviews to gain deeper insights into their experiences and perceptions. The findings reveal that nurses value training programs that are comprehensive, practical, and reflective of real-world scenarios. Satisfaction among nurses is heightened when training leads to increased confidence, competence, and ultimately, a positive impact on patient outcomes. The study also highlights the importance of continuous support and resources as essential elements that facilitate the successful application of training in clinical settings. The findings of this study are expected to provide valuable insights into how training programs can be enhanced to ensure effective pain management in clinical settings, ultimately improving patient outcomes. By identifying and addressing the factors that facilitate or hinder the transfer of training, this research aims to contribute to the development of more effective educational strategies in nursing practice.